Recommender systems: The Effect of Information Privacy Concerns and User Trust on Information Disclosure Intentions - Al abdullateef, Hafsa (2016)
In recent times, recommender systems are being used increasingly by many online applications and e-commerce websites. A significant motivation for adopting this technology is to provide users with personalised products or services based on their profiles. However, research has indicated that information privacy has become a major concern for recommender system users, and this, in turn, has affected their intention to reveal personal information to recommender systems. On the other hand, trust in recommender systems can play an important role in mitigating this effect and influencing behavioural intentions. This study aims to explore the relationship between privacy concerns, trust and the intent to disclose information in the context of recommender systems. It also examines the effect on users’ intentions of the perceived value of online personalisation and user satisfaction. The study employs a quantitative approach to examine the relationship between the factors that influence users’ behavioural intentions. The study data was collected from 248 respondents through an online survey, and the research model and hypotheses were tested using structural equation modelling. The results indicate that the direct effect of privacy concerns on users’ intentions is insignificant. In addition, the findings confirm the role of trust in mediating the effect of privacy concerns on users’ information disclosure intentions. The results also show that trust and the perceived value of online personalisation are the most influential factors.